Studi Eksperimen Dan Komputasi Senyawa Organik Sebagai Inhibitor Korosi : A Review - Maidawati, Maidawati (LPPM Universitas Dharma Andalas, 2023)
Modeling organic compounds with computational software is an option for researchers before conducting experiments in the laboratory. This helps to understand the mechanism of corrosion inhibition of metals on an atomic and molecular scale. Some of the common computational techniques used are DFT theory, MD and Monte carlo simulations. According to the literature, choosing organic compounds through modeling helps researchers determine the efficiency of the right inhibitor, saving time and money. Another advantage of this computational model is that it can easily determine the active sites/adsorption sites and the orientation of organic compounds. This review discusses indicators of corrosion inhibition contained in several computational models. The mechanism of corrosion inhibition by natural compounds and the types of inhibition of compounds are also discussed through polarization potentiodynamics.